Parenting Stress in Families of Children With ADHD: A Meta-Analysis. (March 2013) - Theule, Jennifer; Wiener, Judith; Tannock, Rosemary; Jenkins, Jennifer M.
Meta-analyses were conducted to examine findings on the association between parenting stress and ADHD. Predictors comprising child, parent, and contextual factors, and methodological and demographic moderators of the relationship between parenting stress and ADHD, were examined. Findings from 22 published and 22 unpublished studies were included. Results confirmed that parents of children with ADHD experience more parenting stress than parents of nonclinical controls and that severity of ADHD symptoms was associated with parenting stress. Child co-occurring conduct problems and parental depressive symptomatology predicted parenting stress. Parents of children with ADHD experienced no more parenting stress than parents of other clinically referred children. Little difference in parenting stress was found between mothers and fathers, but child gender was a significant moderator of parenting stress, with lower stress levels in samples with higher proportions of girls.